CHROMATOGRAPHIC SYSTEM SUITABILITY TESTING: INFLUENCE OF CORRECTION FACTORS AND LATE ELUTING PEAKS OF IMPURITIES ON THE REQUIREMENT FOR THE SIGNAL-TO-NOISE RATIO (REVIEW) - N. A. Epshtein (Разработка и регистрация лекарственных средств, 2019)
Introduction. In case of methods of impurities determination quite often there are problems connected both with establishment and with check of implementation of the requirement to necessary sensitivity of a chromatographic system.Text. Influence of correction factors and late eluting peaks of impurities on the requirement for the signal-to-noise ratio (S/N) for chromatographic system suitability testing is considered.Conclusion. The recommendations are provided how to detect situations at which the requirement of S/N≥10 is insufficient for reliable detecting peaks of all impurities (related substances) and therewith how to correct concentration of test solution and/or the requirement to S/N for system suitability testing.